Gay Community, Gay Identity and the Translated Text - Harvey, Keith (TTR)

(untitled) (Association canadienne de traductologie, 2000)
AbstractGay Community, Gay Identity and the Translated Text — In this paper, the author explores the multiple intersections of the notion "gay community" and "gay identity" with the problematic of translation. First, the notions of "community" and "identity" themselves are explored for their theoretical, political and personal ramifications for the gay subject. It is argued that the two notions engage in a constant process of redefinition in relation to each other and, in particular, that they can be seen to overlap if their respective concrete/imagined and internal/external dimensions are taken account of. The author goes on to suggest how translated literature represents a crucial site for the gay person's elaboration of a distinct subjectivity. Then, an example (Spanish-English) is given of a text whose exploration of emerging gay selfhoof is enhanced in translation. Finally, a passage (English-French) is studied in its source and target versions in order to identify the pressures that different cultural conceptions of sexual identity bring to bear upon textual products.